2017
DOI: 10.15406/aovs.2017.07.00235
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Prevalence of Refractive Errors among Children in Lower Primary Schools in Darnah City, Libya

Abstract: Introduction: Refractive error is a one of the most common problem among children which may lead to blindness. Refractive errors cannot be prevented, but they can be diagnosed early by a routine eye examination and treated with corrective glasses, contact lenses or refractive surgery.Objective: To determine the prevalence of refractive errors among school children attending lower primary school in Darnah city eastern part of Libya and the frequency of the various types of refractive errors, and their associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(25 reference statements)
0
8
2
1
Order By: Relevance
“…[8][9][10][11][12] This finding was also similar with the study done in Libya which showed 51.9% females and 45.7% males. 13 However, this study finding is different from the study done in both Nepal and India which reported more male participants than female participants. [14][15][16][17] Maximum female participants in the current study could be because young females report more visual symptoms and also attain puberty earlier as compared to males.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…[8][9][10][11][12] This finding was also similar with the study done in Libya which showed 51.9% females and 45.7% males. 13 However, this study finding is different from the study done in both Nepal and India which reported more male participants than female participants. [14][15][16][17] Maximum female participants in the current study could be because young females report more visual symptoms and also attain puberty earlier as compared to males.…”
Section: Discussioncontrasting
confidence: 96%
“…Similarly, the different studies also observed that maximum number of participants were from urban than rural area. 9,13,17,20 One study found more participants from the rural area. 15 The children living in urban areas have to do lot of near work activities and also the duration of outdoor games was less as compared to children from rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the characteristics of studies included in the systematic review is presented in Table S2 . Briefly, seven studies were conducted in Ghana, 38 , 39 , 40 , 41 , 42 , 43 , 44 six in Ethiopia, 45 , 46 , 47 , 48 , 49 , 50 five in Nigeria, 51 , 52 , 53 , 54 , 55 four in South Africa, 56 , 57 , 58 , 59 three from Egypt, 20 , 60 , 61 two each in Kenya, 62 , 63 Burkina Faso 64 , 65 and Sudan, 66 , 67 and one each in Rwanda, 68 Tunisia, 69 Libya, 70 Somalia, 71 Tanzania, 72 Togo, 73 Equatorial Guinea, 74 Morocco, 75 Uganda, 76 Malawi 77 and Benin 78 (Figure 2 ). Forty of the studies were school‐based, and two were population‐based.…”
Section: Resultsmentioning
confidence: 99%
“… Muma et al (2009) 63 Y N Y N Y Y Y N Y Libya 23. Elmajri (2017) 70 Y N Y N N Y Y Y Y Malawi 24. Msiska et al (2009) 77 Y Y Y Y N Y Y Y Y …”
Section: Search Termsunclassified
See 1 more Smart Citation